Respostas

2014-03-21T15:17:13-03:00
Matriz (3x4)

3x4 = 3 linhas por 4 colunas
i = linhas e j = colunas

A =
a11 a12 a13 a14
a21 a22 a23 a24
a31 a32 a33 a34

aij = 2i – 3j

a11 = 2*1 -3*1 = 2 -3 = -1
a12 = 2*1 -3*2 = 2 -6 = -4
a13 = 2*1 -3*3 = 2 -9 = -7
a14 = 2*1 -3*4 = 2 -12 = -10

a21 = 2*2 -3*1 = 4 -3 = 1
a22 = 2*2 -3*2 = 4 -6 = -2
a23 = 2*2 -3*3 = 4 -9 = -5
a24 = 2*2 -3*4 = 4 -12 = -8

a31 = 2*3 -3*1 = 6 -3 = 3
a32 = 2*3 -3*2 = 6 -6 = 0
a33 = 2*3 -3*3 = 6 -9 = -3
a34 = 2*3 -3*4 = 6 -12 = -6

Resultando na Matriz:

A=
-1 -4 -7 -10
1 -2 -5 -8
3 0 -3 -6